Teachers Perceptions of Microteaching and Its Conceptual Implications for Early Childhood Education: A Phenomenological Study - Roby Naufal Arzaqi; Namira Tri Mareta; Najwa Azizah Ramadhani; Ghea Alza Jazilia; Aisah Karunia Rahayu; Esya Anesty Mashudi; Deri Hendriawan (Indonesian Journal of Early Childhood Educational Research (IJECER), 2026)
Educational transformation requires enhancing the professionalism of early childhood education (PAUD) teachers, one approach being microteaching training to develop fundamental teaching skills. However, microteaching is often perceived primarily as a technical exercise, which does not fully align with early childhood learning practices that are relational and developmentally oriented. This study explores PAUD teachers’ understanding of microteaching skills and their conceptual implications for the quality of early childhood learning. A qualitative approach using Interpretative Phenomenological Analysis (IPA) was employed. Six PAUD teachers were purposefully selected as participants. Data were collected through semi-structured interviews and classroom observations, and thematic analysis was conducted systematically, including coding, pattern identification, and validation of themes across participants. Trustworthiness was ensured through triangulation, member checking, and peer debriefing. The findings revealed four main themes: microteaching as non-internalized knowledge, experiential learning and community of practice, the gap between microteaching simulations and the realities of early childhood learning, and relational pedagogy in practice. The results indicate that teachers often perceive microteaching as a primarily technical exercise, whereas early childhood education requires relational, reflective, and contextually grounded pedagogical competencies. This study contributes novel insights into how microteaching is interpreted in practice, highlighting both conceptual and pedagogical implications for teacher training and professional development in early childhood education.